THE SOCIAL AND SCIENTIFIC-PEDAGOGICAL FOUNDATIONS OF DEVELOPING STUDENTS' PROFESSIONAL COMPETENCIES BASED ON SOCIAL-EMOTIONAL LEARNING THROUGH PROJECTS (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This article explores the social and scientific-pedagogical foundations of developing students' professional competencies through the integration of SocialEmotional Learning (SEL) and Project-Based Learning (PBL). In an era where technical knowledge alone is no longer sufficient, fostering emotional intelligence, social skills, and collaborative abilities is essential for professional success. The study highlights how SEL competencies—such as self-awareness, selfmanagement, social awareness, and responsible decision-making—are crucial for students' personal and professional development.